2012
DOI: 10.1111/j.1439-0264.2011.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Purkinje Cells in the Ovine Brain

Abstract: Purkinje cells are involved in many vital functions within the body. Twenty ovine fetuses ranging from 2 to 5 months of gestation, two lambs in the first week after birth and three adult sheep were studied. Sections of the cerebellum were stained with haematoxylin and eosin, cresyl violet and Klüver-Barrera. This study indicates that Purkinje cells began to appear after the 15(th) week of gestation. There were varying degrees of development of Purkinje cells in different zones of the cerebellum. Our findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The first trimester occurs prior to Purkinje cell genesis and so would affect precursor cells, whereas the third trimester exposure occurs after the genesis of Purkinje cells, during their post-mitotic differentiation. In sheep prenatal brain development, Purkinje cells have not been identified until after GD 80 (Rees and Harding, 1988; Salouci et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first trimester occurs prior to Purkinje cell genesis and so would affect precursor cells, whereas the third trimester exposure occurs after the genesis of Purkinje cells, during their post-mitotic differentiation. In sheep prenatal brain development, Purkinje cells have not been identified until after GD 80 (Rees and Harding, 1988; Salouci et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Purkinje cells are widely studied in neuronal investigations and are one of the most important cells in the cerebellum since they have many connections with different areas in the brain, are the only output neuron of the cerebellar cortex and are involved in many vital functions, including the coordination of sensory input and motor movement, memory, analysis of auditory information, and neurosteroid formation (Salouci et al, 2012). Although extensive research in the field of alcohol neuoroteratogenesis has demonstrated a detrimental effect on developing Purkinje cells (Cragg and Phillips, 1985; Goodlett and Eilers, 1997; Goodlett et al, 1990b; Goodlett et al, 1998; Light et al, 2002a; Maier et al, 1999; Maier and West, 2001; Pauli et al, 1995; Ramadoss et al, 2007a; Ramadoss et al, 2007b) , and the cerebellum appears to be particularly vulnerable to alcohol exposure during development (Autti-Ramo et al, 2002; Bonthius and West, 1990; Goodlett et al, 1990a; Goodlett et al, 1990b; Hamre and West, 1993; Light et al, 2002b; Ramadoss et al, 2007a; Ramadoss et al, 2007b; West et al, 1990), little is known about underlying potential mechanisms for these effects.…”
Section: Introductionmentioning
confidence: 99%
“…The similarity in structure and scale between ovine and human brain vasculature (with the exception of the extradural rete mirabilis) allowed for the development of a permanent and transient middle cerebral artery sheep stroke model [ 8 ]. Due to its constituent Purkinje Cells, the cerebellum is an area studied for its involvement in coordination of sensory input, motor movement, memory processes and connections with cochlear nuclei [ 9 ]. It is of further interest due to its sparing in Batten Disease [ 10 ] and its dysplasia in congenital Schmallenberg Virus Infection [ 11 ].…”
Section: Introductionmentioning
confidence: 99%